1997
DOI: 10.1038/sj.cdd.4400226
|View full text |Cite
|
Sign up to set email alerts
|

Less death in the dying

Abstract: Diseases associated with aging are now the primary causes of death in developed countries. This is in part due to the long recognized exponential association of cancer with age and perhaps to a deterioration of the immune system with advanced age. Both prevention of tumorigenesis and immune function are critically dependent on apoptosis. In this study we examined apoptosis in mice of various age following gamma irradiation. We found a striking agedependent decrease in radiation-induced apoptosis in splenic lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…This was seen clearly in the breast cancer cases and in unaffected women with a family history of cancer, but was also apparent in the unrelated control group, although the number of older controls was small. Polyak et al (1997) observed a reduced apoptotic response of lymphocytes to 5 Gy radiation in mice as they aged, and suggested that similar data on humans would be of interest. Suh et al (2002) found a reduced apoptotic response in rat liver cells exposed to methyl methane-sulphonate.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This was seen clearly in the breast cancer cases and in unaffected women with a family history of cancer, but was also apparent in the unrelated control group, although the number of older controls was small. Polyak et al (1997) observed a reduced apoptotic response of lymphocytes to 5 Gy radiation in mice as they aged, and suggested that similar data on humans would be of interest. Suh et al (2002) found a reduced apoptotic response in rat liver cells exposed to methyl methane-sulphonate.…”
Section: Discussionmentioning
confidence: 78%
“…Polyak et al (1997) and Suh et al (2002), based on rodent data, that such a reduction may play an important role in age-associated disease processes. In relation to cancer specifically, this hypothesis is further supported by the reduced apoptotic response seen in breast cancer patients vs normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waf1 can occur as early as dysplastic aberrant crypt foci, the earliest detectable histological abnormalities and putative precursors of colon cancer (Polyak et al, 1996). We have demonstrated that PKC-d upregulates p21…”
Section: Kip2mentioning
confidence: 85%
“…1B). By using radioactive thymidine and other markers of proliferation, it has been shown that the dysplastic cells at the orifices of the crypts have patterns expected of neoplastic cells whereas the cells at the base have normal proliferative patterns (4,5,8).…”
mentioning
confidence: 99%